2021
DOI: 10.7150/jca.54760
|View full text |Cite
|
Sign up to set email alerts
|

Telomere shortening in head and neck cancer: association between DNA demethylation and survival

Abstract: A growing body of evidence indicates that telomere dysfunction is a biological marker of progression in several types of cancer. However, the association between head and neck squamous cell carcinoma (HNSCC) and telomere length (TL) remains unknown. We measured the absolute TL levels in a well-characterised dataset of 211 tumoral vs normal tissues obtained from the same patients by quantitative polymerase chain reaction assay. Normalised TL levels were significantly lower in tumour samples than in normal tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Research has revealed that the ratio of telomere length between HNSCC and normal tissue is substantially linked to disease recurrence rate, with a smaller ratio indicating a higher likelihood of recurrence. [12] Therefore, telomere maintenance holds significant value for predicting HNSCC prognosis. Our study obtained 2093 TMGs from the TelNet database, and differential expression analysis indicated that 272 TMGs were aberrantly expressed in HNSCC, illustrating abnormal regulation of telomeres in HNSCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has revealed that the ratio of telomere length between HNSCC and normal tissue is substantially linked to disease recurrence rate, with a smaller ratio indicating a higher likelihood of recurrence. [12] Therefore, telomere maintenance holds significant value for predicting HNSCC prognosis. Our study obtained 2093 TMGs from the TelNet database, and differential expression analysis indicated that 272 TMGs were aberrantly expressed in HNSCC, illustrating abnormal regulation of telomeres in HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…[11] In HNSCC, recent studies have shown that shortened telomere length and subsequent low levels of 5-hydroxymethylcytosine and 10 to 11 translocation expression may contribute to the development of HNSCC. [12]…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported that 5-hmC may be associated with human cancer [ 22 , 23 ]. In the present study, the 5-hmC level of the hub genes in CRC patients was different from that in healthy patients.…”
Section: Discussionmentioning
confidence: 99%
“…The obtained results also demonstrate a relationship between interchromatid TL asymmetry and chromosome 5hmC patterns: the longer telomere was predominantly present in the hydroxymethylated sister chromatid, while the non-hydroxymethylated sister chromatid mostly featured a shorter telomere. Recent studies on mouse embryonic stem cells, human blood cells and head and neck squamous cell carcinomas have demonstrated the role of TET hydroxylases and 5hmC in the maintenance of telomere homeostasis, including that occurring through telomere recombination [ 48 , 49 , 50 , 51 ]. In our recent study on chromosomes from human cytotrophoblast cells, an immense heterogeneity of 5hmC patterns has been demonstrated: different types of chromosomal 5hmC accumulation—hydroxymethylation, hemihydroxymethylation and nonhydroxymethylation with no specificity of each accumulation type to any particular chromosome in a given metaphase plate [ 42 ].…”
Section: Discussionmentioning
confidence: 99%